Trapezoidal structure for residue-free filling and patterning - Kim, M. Joon; Song, Seokyong; Kwon, S. Joon; Lee, Hong H. (AMER CHEMICAL SOC, 2007)
A trapezoidal structure is introduced to fill microchannels with a liquid by simple dip-coating without leaving any residue on the other parts of the surface. This selective filling is in turn used for patterning by direct transfer of the filled liquid onto a substrate followed by curing. This patterning leaves no residual layer that most of the lithographies based on a mold have to contend with. For the selective filling, the liquid contact angle has to be high, but a high contact angle can cause instability of the liquid filament in the channel. The trapezoidal structure widens the window of the stability in terms of the contact angle and the channel aspect ratio. A theoretical result is obtained for the stability. Experimental results are also presented to show that the selective filling and patterning can be realized for the channels with an aspect ratio lower and a contact angle higher than those allowed for rectangular channels. The surface curvature of the filled liquid can be controlled by manipulating the drawing speed in the dip coating.
Keywords: WETTING MORPHOLOGIES; LITHOGRAPHY; FABRICATION; POLYMERS; SURFACE